ANALISIS DAMPAK PENGGUNAAN TEKNOLOGI VIRTUAL REALITY (VR) DALAM PEMBELAJARAN PENDIDIKAN ISLAM - Readi, Agus (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to analyze the impact of using Virtual Reality (VR) technology in Islamic education, particularly in enhancing the understanding of religious values, spiritual experiences, and active student engagement. Using a Systematic Literature Review (SLR) approach, this study examines and synthesizes relevant research findings published over the past ten years. Data were obtained from various academic journals indexed in Scopus and Sinta that discuss the integration of VR in the context of Islamic education. The analysis was carried out by evaluating the effectiveness, challenges, and pedagogical implications of VR use.The findings show that VR can create immersive and interactive learning environments, thereby increasing students’ learning interest and conceptual understanding in Islamic Religious Education (IRE) subjects. VR has also proven effective in delivering abstract content—such as the Isra Mi’raj journey, the atmosphere of Hajj rituals, or the life of Prophet Muhammad (peace be upon him)—through visual and narrative means, thus strengthening students' spiritual experiences.However, infrastructure limitations, implementation costs, and teachers’ readiness to integrate the technology remain major challenges. In conclusion, VR contributes positively to innovative IRE learning that is contextual and applicable. The implications of this study highlight the need for teacher training, supportive education policies, and the development of VR content based on Islamic values to optimize the effective and sustainable use of this technology in Islamic education. This study also recommends further exploration of the long-term impact of VR use on students' character and moral development